Accuracy and precision of smartphone colorimetry: a comparative analysis in RGB, HSV, and CIELAB color spaces for archaeological research - Yaowarat Sirisathitkul; Natthinee Dinmeung; Wannasan Noonsuk; Chitnarong Sirisathitkul (Science and Technology of Archaeological Research)
This study evaluates the accuracy and precision of color measurements obtained from digital images captured using smartphone cameras, validated against standard color cards under controlled lighting conditions. RGB (Red, Green, Blue) and HSV (Hue, Saturation, Value) parameters were extracted using the Colorimeter application (app) on an iPhone and the PineTools program on a computer. Both methods demonstrated high precision, as indicated by small standard deviations in repeated measurements. Significant deviations from Pantone reference values were also observed in the overestimation of S and underestimation of V values. Notably, the Color Grab app on an Android phone exhibited superior accuracy in extracting H and V values compared to the iPhone. Additionally, the CIELAB parameters measured by the Android app were comparable to those obtained from a portable colorimeter. These findings underscore the utility of smartphone colorimetry for precise on-site color classification, with significant potential applications in cultural heritage and archaeology.